Effectiveness of Various Antiseptic Hand Soaps in Reducing Skin Bacterial Counts - Fadhila Azzahra, Delima; Samira, Jihan (Journal of World Science, 2026)
Hands are the body part most frequently exposed to environmental bacteria and play an important role in disease transmission. Handwashing with antiseptic soap is an effective method for reducing bacterial contamination on the skin. Antiseptic soaps containing chloroxylenol, povidone-iodine, and chlorhexidine gluconate are widely used due to their broad-spectrum antimicrobial activity. However, the comparative effectiveness of these three antiseptic agents remains unclear. This experimental study employed a group pre-test and post-test design involving 27 students from the Faculty of Dentistry, Trisakti University. The respondents were divided into three groups based on the type of antiseptic soap used: 0.5% chloroxylenol, 7.5% povidone-iodine, and 0.5% chlorhexidine gluconate, with nine respondents in each group. The number of bacterial colonies on the hands was assessed before and after handwashing using the swab method. Data were analyzed using the Wilcoxon signed-rank test and the Kruskal–Wallis test. All three antiseptic soaps demonstrated a significant reduction in bacterial colony counts. In the chloroxylenol group, the median colony count decreased from 100 CFU to 22 CFU (p = 0.018); in the povidone-iodine group, from 11 CFU to 0 CFU (p = 0.008); and in the chlorhexidine gluconate group, from 200 CFU to 61 CFU (p = 0.008). Based on the percentage reduction, povidone-iodine showed the greatest decrease (99.74%), followed by chloroxylenol (79.30%) and chlorhexidine gluconate (51.97%). However, comparisons of bacterial colony reduction among the three groups showed no statistically significant difference in effectiveness (p = 0.481).